Land configurations in surface drip irrigation for enhancing productivity, profitability and water-use efficiency of Indian mustard (Brassica juncea) under semi-arid conditions - RATHORE, S S; SHEKHAWAT, KAPILA; RAJANNA, G A (The Indian Journal of Agricultural Sciences, 2020)
The aim of the experiment was to maximize water-use efficiency and resultant crop productivity through surface drip irrigation under modified land techniques in arid- and semi-arid conditions of India. To address these issues, field study was undertaken on Indian mustard [Brassica juncea (L.) Czern. & Coss.] with surface drip irrigation under various land configuration techniques to enhance water-use efficiency, crop productivity and profitability. Results of the study revealed that flat sowing drip irrigation system in 60/30 and 30/60 cm land configuration resulted in highest seed yield (141 to 161 %), oil productivity (139 to 150%) and water-use efficiency of mustard seed (141 to 162 %) over flat 90/60cm land configuration. Better growth and yield attributes of Indian mustard were also recorded in land configuration of flat sowing in 60/30 and 30/60cm. Maximum net return of ` 102Ã—103 obtained at 30/60cm flat sowing followed by flat sowing at 60/30cm land configuration over other land configurations under drip irrigation. Likely, sowing of mustard at 30/60cm followed by 60/30cm flat land configuration with surface drip irrigation produced highest root biomass (79 to 94%), root length density (75to 86%), root volume density (135 to 169%) and root mass density (65 to 125%) over 90/60cm flat land configuration. Among ridge and furrow land configuration, 30/60cm ridge and 60/30cm furrow sowing found better in producing highest seed and oil yields, better economics over 90/60cm furrow.